MANAGEMENT OF ALTERNATIVE MEDIA KAWALCOVID19 AS A SOURCE OF INFORMATION DURING THE COVID-19 PANDEMIC - Adi Wiguna; Reni Nuraeni (MediaTor (Jurnal Komunikasi), 2021)
The world is currently plagued by the Covid-19 pandemic. This situation causes the need for information as an essential thing for the public. KawalCOVID19 is one of the alternative media that contains information, education, and verification purposes regarding the Covid-19 pandemic in Indonesia, therefore good management of alternative media must be carried out by its managers. The purpose of this research is to find out how the management of KawalCOVID19 alternative media handles information about the Covid-19 pandemic. This research is a qualitative study with a descriptive method. The result of this study is that KawalCOVID19's alternative media management from the aspect of content, production, and distribution has a variety of unique features that distinguish it from mainstream media. In terms of content, KawalCOVID19 is neutral and offers a graphical display that makes it easier for readers to find out more information related to the Covid-19 pandemic. In the production aspect, the entire production process is carried out in full online collaboration of data, content, and technology teams. In the distribution aspect, KawalCOVID19 collaborates with various communities and NGOs, and uses social media to reach a wider audience. The management of KawalCOVID19 which is different from most other media, especially mainstream media during the pandemic shows that further studies are still viable regarding alternative media during the pandemic.